2000
DOI: 10.1044/jslhr.4301.144
|View full text |Cite
|
Sign up to set email alerts
|

Childrens’ Phoneme Identification in Reverberation and Noise

Abstract: This study assessed the effects of reverberation, noise, and their combination on listeners' identification of consonants and vowels in naturally produced nonsense syllables presented at different sensation levels (re: speech recognition threshold). A secondary purpose of this study was to assess listeners' identification of voicing, manner, and place of articulation for consonants at 50 dB SL in the reverberation, noise, and combined conditions. Listeners, aged 6-30 years, identified consonant-vowel-consonant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
173
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(198 citation statements)
references
References 41 publications
23
173
0
2
Order By: Relevance
“…For example, Hazan and Barrett (2000) found that children were more consistent in identification when multiple cues were available compared to when only a single cue was available suggesting that children lack the flexibility to use whatever cue was available. Nittrouer et al (2000) came to a similar conclusion in a study of 5-and 7-year-old children, and Johnson's (2000) observation that even 15-year-olds performed more poorly than adults in speech identification in the presence of noise or reverberation also is consistent with this idea.…”
Section: Flexibility In the Use Of Acoustic Informationsupporting
confidence: 73%
“…For example, Hazan and Barrett (2000) found that children were more consistent in identification when multiple cues were available compared to when only a single cue was available suggesting that children lack the flexibility to use whatever cue was available. Nittrouer et al (2000) came to a similar conclusion in a study of 5-and 7-year-old children, and Johnson's (2000) observation that even 15-year-olds performed more poorly than adults in speech identification in the presence of noise or reverberation also is consistent with this idea.…”
Section: Flexibility In the Use Of Acoustic Informationsupporting
confidence: 73%
“…At the nonspeech level, this is in line with (1) physiological animal studies showing that neural coding for temporal aspects of the stimulus reaches maturity later than neural coding for frequency selectivity (Eggermont, 1996), and with (2) behavioral auditory studies in humans providing evidence for a more prolonged development of the sensitivity for temporal than for nontemporal auditory cues (Hartley, Wright, Hogan, & Moore, 2000), even after accounting for the effect of procedure-related skills (Dawes & Bishop, 2008). At the speech level, it coincides with behavioral speech perception studies demonstrating that the identification of stop consonants is not yet mature by the age of 11 (Hazan & Barrett, 2000;Johnson, 2000;Krause, 1982;Simon & Fourcin, 1978;Medina, Hoonhorst, Bogliotti, & Serniclaes, 2010), whereas the identification of vowels does only slightly, though not significantly, improves towards adolescence (Pursell, Swanson, Hedrick, & Nabelek, 2002;Ohde, Haley, & McMahon, 1996;Johnson, 2000, but see Walley and Flege, 1999). Further elaboration on this topic is needed, but the indication that perception of sounds with temporal versus nontemporal cues follows different maturational trajectories in both normal and dyslexic readers, may have practical implications with regard to auditory temporal training programs.…”
Section: Discussionmentioning
confidence: 48%
“…A literatura indica que o reconhecimento de fala das crianças normo-ouvintes é mais afetado por condições adversas como no ruído e/ou em ambiente reverberante quando comparadas aos adultos e esse desempenho pior em crianças para percepção da fala no ruído é esperado até os dez ou doze anos de idade (13)(14)(15)(16)(17)(18)(19)(20)(21). Os estudos supracitados não utilizaram ruído difuso, como as quatro caixas de campo livre adotadas no presente trabalho.…”
Section: Discussionunclassified